(untitled) (Scientific journal of the Fergana State University, 2025)
The article deals with the phonetic and stylistic features of the growth event in the poems of the Khorasan style. The Tajik language has a long history and reached the height of its development in the time of the Somonites. As has become clear from the reading of the works and this analysis, we can observe a phenomenon of growth in the poetry of representatives of the Khorasan style, some of which continues to this day. In these works, the letters a, o, i, i, and , y, ё or etc., which we have analysed above, have been joined by other letters (vowels, consonants). Although this event is more characteristic of phonetics, it provides stylistic, morphological and expressive features of the poets’ poetry. At the same time, some increased phonemes have become a means by which we can learn about the origins of the common Dari-Tajik spoken language and its styles. Also, thanks to the development and use of the Khorasan style in poetry, poets created sonorous synonyms for some words, which, thanks to their poems, have been preserved in the vocabulary of the Tajik literary language to this day.